Biofunctionalised bacterial cellulose scaffold supports the patterning and expansion of human embryonic stem cell-derived dopaminergic progenitor cells - Miranda Robbins (BMC, 2021)
Abstract Background Stem cell-based therapies for neurodegenerative diseases like Parkinson’s disease are a promising approach in regenerative medicine and are now moving towards early stage clinical trials. However, a number of challenges remain including the ability to grow stem cells in vitro on a 3-dimensional scaffold, as well as their loss, by leakage or cell death, post-implantation. These issues could, however, be helped through the use of scaffolds that support the growth and differentiation of stem cells both in vitro and in vivo. The present study focuses on the use of bacterial cellulose as an in vitro scaffold to promote the growth of different stem cell-derived cell types. Bacterial cellulose was used because of its remarkable properties such as its wettability, ability to retain water and low stiffness, all of which is similar to that found in brain tissue. Methods We cultured human embryonic stem cell-derived progenitor cells on bacterial cellulose with growth factors that were covalently functionalised to the surface via silanisation. Epifluorescence microscopy and immunofluorescence were used to detect the differentiation of stem cells into dopaminergic ventral midbrain progenitor cells. We then quantified the proportion of cells that differentiated into progenitor cells and compared the effect of growing cells on biofunctionalised cellulose versus standard cellulose. Results We show that the covalent functionalisation of bacterial cellulose sheets with bioactive peptides improves the growth and differentiation of human pluripotent stem cells into dopaminergic neuronal progenitors. Conclusions This study suggests that the biocompatible material, bacterial cellulose, has potential applications in cell therapy approaches as a means to repair damage to the central nervous system, such as in Parkinson’s disease but also in tissue engineering.